Existência de atrator global para equações de Navier-Stokes sobre alguns domínios ilimitados em R2. - Silva, Jarbas Dantas da (2014)
In this work, we study the Navier-Stokes flow in R2 8> >>>>>><> >>>>>>: @u @t − ⌫!u + (u ·r)u + rp = f em ⌦ ⇥ [0,+1) , divu = r· u = 0 em ⌦⇥ [0,+1) , u = 0 sobre @⌦ ⇥ [0,+1) , u(·, 0) = u0 em ⌦, in an unbounded domain such that the Poincar´e s inequality is holds, i.e., there is a constant #1 > 0 such that we have the following inequality Z⌦ $2dx  1 #1 Z⌦ |r$|2dx, for all $ 2 H1 0 (⌦). We show the existence of global attractor in the natural phases spaces for this system exploring the energy equation of the problem